Microstructure, crystallography and diagenetic alteration in fossil ostrich eggshells from Upper Palaeolithic sites of Indian peninsular region. (May 2016) - Jain, Sonal; Bajpai, Sunil; Kumar, Giriraj; Pruthi, Vikas
Graphical abstract: Highlights: Dolomitization in fossil eggshells from Upper Paleolithic sites revealed by EBSD. Calcite crystallization and microstructure of fossilized eggshell layers observed. Determination of nature and extent of diagenesis in fossils eggshells. Abstract: Biominerals studies are of importance as they provide an understanding of natural evolutionary processes. In this study we have investigated the fossil ostrich eggshells using Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD) and Electron Backscatter Diffraction (EBSD). SEM studies demonstrated the ultrastructure of fossil eggshells and formation of calcified cuticular layer. The presence of calcified cuticle layer in eggshell is the basis for ancient DNA studies as it contains preserved biomolecules. EBSD accentuates the crystallographic structure of the ostrich eggshells with sub-micrometer resolution. It is a non-destructive tool for evaluating the extent of diagenesis in a biomineral. EBSD analysis revealed the presence of dolomite in the eggshells. This research resulted in the complete recognition of the structure of ostrich eggshells as well as the nature and extent of diagenesis in these eggshells which is vital for genetic and paleoenvironmental studies.